Climate Change and the Bottom Line: Delivering Sustainable Buildings at Market Rate. (3rd January 2018) - Cohen, Adam; Snell, Clarke
Abstract : Sustainable building need not be more expensive or time‐consuming than the alternative.Adam Cohen – co‐founder of Virginia firm Structures Design/Build – has a proven track record of completing a range of building types affordably and on schedule, even achieving Passive House standards within budget when they were not part of the client's original brief. How? As he explains to Guest‐EditorClarke Snell, the answer is lean IPD (integrated project delivery). By involving all stakeholders from the start and making optimum use of BIM (building information modelling), it improves efficiency and keeps costs in check.